Oral Vaccination of Mice With Trichinella spiralis Putative Serine Protease and Murine Interleukin-4 DNA Delivered by Invasive Lactiplantibacillus plantarum Elicits Protective Immunity - Xue, Ying; Zhang, Bo; Wang, Nan; Huang, Hai-Bin; Quan, Yu; Lu, Hui-Nan; Zhu, Zhi-Yu; Li, Jun-Yi; Pan, Tian-Xu; Tang, Yue; Jiang, Yan-Long; Shi, Chun-Wei; et al. (Frontiers in Microbiology, 2022)
Trichinellosis is a serious zoonotic parasitic disease caused by Trichinella spiralis (T. spiralis) that causes considerable economic losses for the global pig breeding and food industries. As such, there is an urgent need for a vaccine that can prevent T. spiralis infection. Previous studies have reported that recombinant invasive Lactococcus lactis (LL) expressing either Staphylococcus aureus Fibronectin Binding Protein A (LL-FnBPA+) can transfer DNA vaccines either directly to dendritic cells (DCs) to across an epithelial cell monolayer, leading to significant higher amounts of heterologous protein expression compared to non-invasive Lactococcus lactis. In this study, the invasive bacterium Lactiplantibacillus plantarum (L. plantarum) expressing FnBPA was used as a carrier to deliver a novel oral DNA vaccine consisting of T. spiralis adult putative serine protease (Ts-ADpsp) and murine interleukin (IL)-4 DNA to mouse intestinal epithelial cells. Experimental mice were orally immunized 3 times at 10-day intervals. At 10 days after the last vaccination, mice were challenged with 350 T. spiralis infective larvae by oral inoculation. Immunization with invasive L. plantarum harboring pValac-Ts-ADpsp/pSIP409-FnBPA induced the production of anti-Ts-ADpsp-specific IgG of serum, type 1 and 2 helper T cell cytokines of mesenteric lymph node (MLN) and spleen, and secreted (s) IgA of intestinal lavage and decreased T. spiralis burden and intestinal damage compared to immunization with non-invasive L. plantarum expressing Ts-ADpsp (pValac-Ts-ADpsp/pSIP409). Thus, invasive L. plantarum expressing FnBPA and IL-4 stimulates both mucosal and cellular immune response to protect against T. spiralis infection, highlighting its therapeutic potential as an effective DNA vaccine for trichinellosis.